PENYULUHAN DAN WORKSHOP PEMBUATAN LOTION ANTI NYAMUK DARI DAUN SEREH DAN DAUN PANDAN DI DESA GEDANGAN KECAMATAN GROGOL KABUPATEN SUKOHARJO: Pembuatan Lotion Anti Nyamuk (STIKes Mitra Keluarga, 2023)
Gedangan Village is located in Grogol District, Sukoharjo Regency. During the rainy season, this village is often hit by floods. This situation causes many puddles of water which can become nests for mosquitoes. This problem is what causes the emergence of Dengue Fever (DHF) in the area. The aim of this activity is to provide education about dengue fever and provide training in making Anti-Mosquito Lotion using Lemongrass and Pandan Leaves. The method of this activity is carried out by providing education about Dengue Fever, preventing dengue fever using the herbal ingredients Lemongrass Leaves and Pandan Leaves as well as training in making Anti-Mosquito Lotion using TOGA plants taken from local villages. Participants were put into groups for training in making Anti-Mosquito Lotion. The success of the activity is by looking at the results of the training and analyzing the Pre-Test and Post-Test statistically. Community service activities were declared successful with a pre-test score of 78.28 and a post-test of 92.80 with a value of Sig.0.002.